Anti-myelin oligodendrocyte glycoprotein antibodies: Magnetic resonance imaging findings in a case series and a literature review. Issue 1 (February 2018) - Michaela, Cellina; Vincenza, Fetoni; Matteo, Ciocca; Marta, Pirovano; Giancarlo, Oliva
Myelin oligodendrocyte glycoprotein is a protein exclusively expressed on the surface of oligodendrocytes and myelin in the central nervous system. Antibodies against myelin oligodendrocyte glycoprotein were initially detected in children with demyelinating syndromes, and more recently reported in a broad spectrum of central nervous system demyelinating diseases in adults, including neuromyelitis optica spectrum disorders and bilateral optic neuritis. Patients with myelin oligodendrocyte glycoprotein antibody-associated demyelination appear to have unique clinical and radiological features. To the best of our knowledge a series of Italian patients with optic neuritis and positivity to myelin oligodendrocyte glycoprotein antibodies has not yet been reported and the paper on myelin oligodendrocyte glycoprotein antibodies are more focused on clinical features, diagnosis and outcome than on the radiological appearance, so we want to retrospectively report magnetic resonance imaging features of a group of eight patients, who came to our Ophthalmologic Emergency Department for optic neuritis and were found seropositive for myelin oligodendrocyte glycoprotein antibodies, comparing our data with the findings described in the literature.